The Existence of The Mystique of The Protected Forest as A Form of Student Character Education Value - Resdianto Permata Raharjo; Alfian Setya Nugraha; Sharifah Fazliyaton Shaik Ismail; Suyatno Suyatno; Anas Ahmadi; Irham Thufani Anshori (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2024)
Objective: The purpose of this study is to explore the protected forest mystique in Wonosalam, Jombang Regency, as a form of character education for students. The protected forest's myths promote personality development by incorporating moral principles, such as, patience, honesty, and sincerity into character education. The novelty of the research highlights local myths and traditions that are rich in spiritual, material, and moral qualities, which in turn help students develop their character and preserve their culture in the face of globalization. Method: Employed in this research is a qualitative approach, bolstered by data collection techniques such as interviews with the village head, recordings of stories, documentation of the surrounding environment and observation of Wonosalam village. The data analysis technique used is descriptive. The research focuses on the myth of the Wonosalam protected forest. Results: Analysis based on Niels Mulder's mystical theory and Imam Ghazali's character education concept show that the protected forest mystique has interrelated material, spiritual, and moral dimensions. These mystical stories contain moral values such as honesty, patience, and sincerity that are crucial for students' character education. By understanding these mystics, students can develop a balanced character and appreciate traditional values and local spirituality. Novelty: this research lies in the approach that integrates mysticism with Islamic value-based character education. The technique that combines Islamic value-based character education with mysticism is what makes this research novel.